'Within Ring' Concept Treatment for Displaced H-Shaped Type IVb Fragility Fractures of the Pelvis. (15th October 2021) - Yanagisawa, Yohei; Eda, Yusuke; Teruya, Shotaro; Gamada, Hisanori; Yamazaki, Masashi
Abstract : Introduction . Sacroiliac rod fixation (SIRF) preserves the mobility of L5/S1 (lumber in the pelvis), as a surgical procedure for high-energy pelvic ring fractures. The concept of SIRF method without pedicle screws into L4 and L5 is called 'within ring' concept. Case Presentation . We report here the clinical results of 'within ring' concept treatment with sacroiliac rod fixation for a case of displaced H-shaped Rommens and Hofmann classification type IVb fragility fractures of the pelvis (FFP), which A 79-year-old woman had been difficult to walk due to pain that had been prolonged for more than one month since her injury. The patient was successfully treated with SIRF, no pain waking with a walking stick and returned to most social activities including living independently within 6 months of the operation. Conclusion . SIRF is useful because it can preserve the mobility in the lumbar pelvis; not including the lumbar spine in the fixation range like spino pelvic fixation is a simple, safe, and low-invasive internal fixation method for displaced H-shaped type IVb fragility fractures of the pelvis.